Haspin kinase regulates microtubule-organizing center clustering and stability through Aurora kinase C in mouse oocytes - Balboula, Ahmed Z; Nguyen, Alexandra L; Gentilello, Amanda S; Quartuccio, Suzanne M; Drutovic, David; Solc, Petr; Schindler, Karen (Journal of cell science, 2016)
Meiotic oocytes lack classic centrosomes and, therefore, bipolar spindle assembly depends on clustering of acentriolar microtubule-organizing centers (MTOCs) into two poles. However, the molecular mechanism regulating MTOC assembly into two poles is not fully understood. The kinase haspin (also known as GSG2) is required to regulate Aurora kinase C (AURKC) localization at chromosomes during meiosis I. Here, we show that inhibition of haspin perturbed MTOC clustering into two poles and the stability of the clustered MTOCs. Furthermore, we show that AURKC localizes to MTOCs in mouse oocytes. Inhibition of haspin perturbed the localization of AURKC at MTOCs, and overexpression of AURKC rescued the MTOC-clustering defects in haspin-inhibited oocytes. Taken together, our data uncover a role for haspin as a regulator of bipolar spindle assembly by regulating AURKC function at acentriolar MTOCs in oocytes.
Keywords: MTOC; transport proteinů; Aurora kinase; Haspin; Oocyte; Microtubule-Organizing Center; Aurora kinasa C; protein-serin-threoninkinasy; Metaphase; Mice; organizační centrum mikrotubulů; Intracellular Signaling Peptides and Proteins; Spindle Apparatus; aparát dělícího vřeténka; Protein Serine-Threonine Kinases; Oocytes; intracelulární signální peptidy a proteiny; zvířata; oocyty; Aurora Kinase C; myši; Protein Transport; Spindle; metafáze; Animals